Spatial biases in residential mobility: Implications for travel behaviour research. (January 2020) - Kamruzzaman, Md.; De Vos, Jonas; Currie, Graham; Giles-Corti, Billie; Turrell, Gavin
Highlights: Contemporary examination of spatial biases in residential mobility. Three indicators of spatial biases (distance, direction, and sector) were investigated. Estimates of the effects of spatial biases on travel behaviour. 70%, 68%, and 62% respondents experienced distance, direction and sector biases respectively. Sector bias reduced the likelihood of switching to more sustainable mode of transport. Abstract: Transport researchers conceptualise residential mobility as a BE intervention because there is the potential for residents to be exposed to a different urban form following relocation. Residential mobility studies therefore overcome the weaknesses of cross-sectional studies in establishing causal links between urban form and travel behaviour. However, what if residential mobility is spatially biased (e.g. a move characterised by a shorter distance, along the direction of home-CBD line, or within a wedge-shaped home sector), and as a result, residents are unable to perceive changes in urban form because their accustomed structural settings (major roads, public transport routes) remain unchanged? This study hypothesises that the true effects of urban form differences on travel behaviour can only be observed if residents overcome the spatial biases in their residential mobility. The research examines the spatial biases of 274 individuals in Brisbane who experienced significant changes in urban form following relocation and estimates the effects of urban form and spatial biases on mode switch behaviour. Results show that 70%, 68%, and 62% of the sample experienced distance, direction and sector biases respectively. Respondents who overcame the sector bias (i.e. experienced a structural change following relocation) were likely to switch to more sustainable mode of transport. The effects of urban form on mode switch behaviour was only evident when movers overcame the sector bias. The findings suggest that, in the presence of strong spatial biases, the true effect of urban form on travel behaviour might be obscured in studies using residential mobility as BE interventions.